Introduction: The Pan-Eurasian Experiment (PEEX) – multidisciplinary, multiscale and multicomponent research and capacity-building initiative - M. Kulmala (Atmospheric Chemistry and Physics, 2015)
The Pan-Eurasian Experiment (PEEX) is a multidisciplinary, multiscale and multicomponent research, research infrastructure and capacity-building program. PEEX has originated from a bottom-up approach by the science communities and is aiming at resolving the major uncertainties in Earth system science and global sustainability issues concerning the Arctic and boreal pan-Eurasian regions, as well as China. The vision of PEEX is to solve interlinked, global grand challenges influencing human well-being and societies in northern Eurasia and China. Such challenges include climate change; air quality; biodiversity loss; urbanization; chemicalization; food and freshwater availability; energy production; and use of natural resources by mining, industry, energy production and transport sectors. Our approach is integrative and supra-disciplinary, recognizing the important role of the Arctic and boreal ecosystems in the Earth system. The PEEX vision includes establishing and maintaining long-term, coherent and coordinated research activities as well as continuous, comprehensive research and educational infrastructure and related capacity-building across the PEEX domain. In this paper we present the PEEX structure and summarize its motivation, objectives and future outlook.